2008
DOI: 10.14742/ajet.1192
|View full text |Cite
|
Sign up to set email alerts
|

A multi-component model for assessing learning objects: The learning object evaluation metric (LOEM)

Abstract: <span>While discussion of the criteria needed to assess learning objects has been extensive, a formal, systematic model for evaluation has yet to be thoroughly tested. The purpose of the following study was to develop and assess a multi-component model for evaluating learning objects. The Learning Object Evaluation Metric (LOEM) was developed from a detailed list of criteria gathered from a comprehensive review of the literature. A sample of 1113 middle and secondary students, 33 teachers, and 44 learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
15

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 39 publications
1
33
1
15
Order By: Relevance
“…A similar study has been carried out by Kay and Knaack (2008), and their principal axis factoring revealed 4 constructs: interactivity, design, engagement, and usability. Francis and Murphy (2008) have carried out a similar study, in which they investigated how instructional designers conceptualize learning objects and their attributes.…”
Section: Conclusion and Recommendationsmentioning
confidence: 67%
See 2 more Smart Citations
“…A similar study has been carried out by Kay and Knaack (2008), and their principal axis factoring revealed 4 constructs: interactivity, design, engagement, and usability. Francis and Murphy (2008) have carried out a similar study, in which they investigated how instructional designers conceptualize learning objects and their attributes.…”
Section: Conclusion and Recommendationsmentioning
confidence: 67%
“…Lau and Peter found that both the user beliefs and attitudes had significant positive relationships with behavioral intention and that behavioral intention accurately predicted the actual use of learning objects. Kay and Knaack (2008) aimed to develop and assess a multicomponent model for evaluating learning objects. A sample of 1113 middle and secondary students, 33 teachers, and 44 learning objects was used to test this model.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Coachrane (2005) tested a modified version of the MERLOT evaluation tool that looked at reusability, quality of interactivity, and potential for teaching, but only final scores are tallied, so the impact of separate components could not be determined. Finally, the reliability and validity of the MERLOT assessment tool has yet to be established [4]. Kay & Knaack (2005, 2007a) developed an evaluation tool based on a detailed review of research on instructional design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Downes considers that only resources that are shareable, digital, modular, interoperable and discoverable can be considered learning objects [Downes, 2004]. Kay & Knaack define Learning objects as "interactive web-based tools that support the learning of specific concepts by enhancing, amplifying, and/or guiding the cognitive processes of learners' [4]." Learning Objects are beneficial for learners as well as developers or instructors as it provides a customized environment for knowledge sharing and development of e-learning course module.…”
Section: Introductionmentioning
confidence: 99%